Suppression of Ribosome Biogenesis by Targeting WD Repeat Domain 12 (WDR12) Inhibits Glioma Stem-Like Cell Growth - Mi, Lanjuan; Qi, Qinghui; Ran, Haowen; Chen, Lishu; Li, Da; Xiao, Dake; Wu, Jiaqi; Cai, Yan; Zhang, Songyang; Li, Yuanyuan; Li, Bohan; Xie, Jiong; et al. (Frontiers in Oncology, 2021)
Glioma stem-like cells (GSCs) are a subset of tumor cells that initiate malignant growth and promote the therapeutic resistance of glioblastoma, the most lethal primary brain tumor. Ribosome biogenesis is an essential cellular process to maintain cell growth, but its regulatory mechanism in GSCs remains largely unknown. Here, we show that WD repeat domain 12 (WDR12), a component of the Pes1-Bop1 complex (PeBoW), is required for ribosome biogenesis in GSCs. WDR12 is preferentially expressed in GSCs compared to non-stem tumor cells and normal brain cells. High levels of WDR12 are associated with glioblastoma progression and poor prognosis. Silencing WDR12 results in the degradation of PeBoW complex components and prevents the maturation of 28S rRNA, thereby inhibiting ribosome biogenesis in GSCs. Subsequently, WDR12 depletion compromises GSC proliferation, inhibits GSC-derived orthotopic tumor growth, and extends animal survival. Together, our results suggest that WDR12 is crucial for ribosome biogenesis in GSCs, and is thus a potential target for GSC-directed therapy of glioblastoma.